Novel LC/MS/MS and High-Throughput Mass Spectrometric Assays for Monoacylglycerol Acyltransferase Inhibitors. (April 2017) - Qi, Jenson; Masucci, John A.; Lang, Wensheng; Connelly, Margery A.; Caldwell, Gary W.; Petrounia, Ioanna; Kirkpatrick, Jennifer; Barnakov, Alexander N.; Struble, Geoffrey; Miller, Robyn; Dzordzorine, Keli; Kuo, Gee-Hong; et al.
Monoacylglycerol acyltransferase enzymes (MGAT1, MGAT2, and MGAT3) convert monoacylglycerol to diacylglycerol (DAG). MGAT1 and MGAT2 are both implicated in obesity-related metabolic diseases. Conventional MGAT enzyme assays use radioactive substrates, wherein the product of the MGAT-catalyzed reaction is usually resolved by time-consuming thin layer chromatography (TLC) analysis. Furthermore, microsomal membrane preparations typically contain endogenous diacylglycerol acyltransferase (DGAT) from the host cells, and these DGAT activities can further acylate DAG to form triglyceride (TG). Our mass spectrometry (liquid chromatography–tandem mass spectrometry, or LC/MS/MS) MGAT2 assay measures human recombinant MGAT2-catalyzed formation of didecanoyl-glycerol from 1-decanoyl-rac-glycerol and decanoyl-CoA, to produce predominantly 1, 3-didecanoyl-glycerol. Unlike 1, 2-DAG, 1, 3-didecanoyl-glycerol is proved to be not susceptible to further acylation to TG. 1, 3-Didecanoyl-glycerol product can be readily solubilized and directly subjected to high-throughput mass spectrometry (HTMS) without further extraction in a 384-well format. We also have established the LC/MS/MS MGAT activity assay in the intestinal microsomes from various species. Our assay is proved to be highly sensitive, and thus it allows measurement of endogenous MGAT activity in cell lysates and tissue preparations. The implementation of the HTMS MGAT activity assay has facilitated the robust screening and evaluation of MGAT inhibitors for the treatment of metabolic diseases.